2018
DOI: 10.1016/j.ijpara.2018.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Validity of the Diplostomoidea and Diplostomida (Digenea, Platyhelminthes) upheld in phylogenomic analysis

Abstract: Higher systematics within the Digenea, Carus 1863 have been relatively stable since a phylogenetic analysis of partial nuclear ribosomal markers (rDNA) led to the erection of the Diplostomida Olson, Cribb, Tkach, Bray, and Littlewood, 2003. However, recent mitochondrial (mt) genome phylogenies suggest this order might be paraphyletic. These analyses show members of two diplostomidan superfamilies are more closely related to the Plagiorchiida La Rue, 1957 than to other members of the Diplostomida. In one of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
69
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(75 citation statements)
references
References 82 publications
6
69
0
Order By: Relevance
“…However, these efforts are not in vain, as they provide a foundation for further sampling that may create the missing life cycle links between larvae and adults in the future. For instance, the species C. marcogliesei was just described for the first time this past year (Locke et al, ), based on adult worms derived from a Hooded Merganser in Montreal, QC. The alignment of our sequences to that of Locke et al have now added a new snail first‐intermediate host record, S. elodes, in addition to a new geographical record of being in Alberta.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these efforts are not in vain, as they provide a foundation for further sampling that may create the missing life cycle links between larvae and adults in the future. For instance, the species C. marcogliesei was just described for the first time this past year (Locke et al, ), based on adult worms derived from a Hooded Merganser in Montreal, QC. The alignment of our sequences to that of Locke et al have now added a new snail first‐intermediate host record, S. elodes, in addition to a new geographical record of being in Alberta.…”
Section: Discussionmentioning
confidence: 99%
“…Recent meta‐ and spatial analyses have shown that our understanding of parasite diversity is biased toward location, time, and parasite class, correlating with when and where taxonomists are most active during their careers, and it is argued that more taxonomists are needed (Poulin, ; Poulin & Jorge, ). Molecular methods have come a long way in allowing faster and more precise species identifications and the ability to make hypotheses about species relationships and evolution considering cryptic morphology.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Brabec et al (2015) generated the mitogenome of two species of diplostomids, and their phylogenetic analyses using amino acids and nucleotides recovered Diplostomidae as the sister group of the Plagiorchiida, although those relationships were supported by a low nodal support value. In a recent study, Locke et al (2018) generated the complete mitochondrial genome of seven additional diplostomoids representing three families and performed a phylogenetic analysis with mitogenomes. To choose between the topologies from the mitochondrial and nuclear phylogenetic analyses, these authors also analysed hundreds of ultra-conserved elements (UCEs) obtained by shotgun sequencing.…”
Section: Ribosomal Vs Complete Mitochondrial Genome Phylogeniesmentioning
confidence: 99%
“…Other studies have generated DNA sequence data from other life cycle stages, mostly cercariae and metacercariae (Blasco‐Costa & Locke, ; Ciparis, Iwanowicz, & Voshell, ; Karamian et al, ; Locke et al, ; Locke, McLaughlin, & Marcogliese, ); however, the limited sequence data from adult forms prevent accurate species‐ or genus‐level diagnoses of the sequenced life cycle stages. While recent molecular phylogenetic studies (Blasco‐Costa & Locke, ; Hernández‐Mena et al, ; Locke et al, ) have indicated the general position of the Cyathocotylidae among other diplostomoidean families, the very limited number of taxa used in these analyses did not allow exploration of questions of evolution and systematics related to geographic distribution, host associations and environmental switches of the group. For instance, no molecular data have been published on any of the genera of cyathocotylids parasitizing non‐avian reptiles and fish as adults.…”
Section: Introductionmentioning
confidence: 99%
“…cycle stages. While recent molecular phylogenetic studies (Blasco-Costa & Locke, 2017;Hernández-Mena et al, 2017;Locke et al, 2018) have indicated the general position of the Cyathocotylidae among other diplostomoidean families, the very limited number of taxa used in these analyses did not allow exploration of questions of evolution and systematics related to geographic distribution, host associations and envi ronmental switches of the group. For instance, no molecular data have been published on any of the genera of cyathocoty lids parasitizing non-avian reptiles and fish as adults.…”
mentioning
confidence: 99%